Building an import/export business - Weiss, Kenneth D. (Kenneth Duane), 1940- (New York : Wiley, 1991)
Shows you how to start your own import/export business, from researching a raw idea to a successful launch to ongoing, profitable business operations. Complete with real-life examples from importers and exporters, it helps you every step of the way, from targeting a market and preparing a business plan to dealing with foreign currencies, shipping procedures, customs requirements, and more. It also shares tips to help you take advantage of NAFTA and other trade pacts, plus online resources to help you start and grow your business.
Jumping into the water : simple scenarios -- Deciding whether this business is for you -- Setting up your business -- Importing : selecting products and suppliers -- Exporting : what comes first, the product, or the market? -- Choosing target markets and finding customers -- Credit, payment, and related concerns -- Shipping, and insuring your goods -- Documents, documents, documents -- Regulations you must know about -- Sources of information and assistance -- Trade with the New Europe -- Appendix A. Outline for a business plan -- Appendix B. Trade contacts -- Appendix C. International trade administration/US&FCS District Offices -- Appendix D. Sample supply agreements.
Includes bibliographical references and index.
oif 27/10/15
Loan
Keywords: Export marketing; Trading companies; International trade